1989
DOI: 10.1038/342934a0
|View full text |Cite
|
Sign up to set email alerts
|

A protein binding to the Jk recombination sequence of immunoglobulin genes contains a sequence related to the integrase motif

Abstract: Site-specific recombination requires conserved DNA sequences specific to each system, and system-specific proteins that recognize specific DNA sequences. The site-specific recombinases seem to fall into at least two families, based on their protein structure and chemistry of strand breakage. One of these is the resolvase-invertase family, members of which seem to form a serine-phosphate linkage with DNA. Members of the other family, called the integrase family, contain a conserved tyrosine residue that forms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 25 publications
2
93
0
Order By: Relevance
“…Therefore, signaling by NOTCH1 can be mediated by its association with RBP-J and potential other factors acting at the promoters. [12][13][14][15] Genetic studies have also suggested a functional association with these two molecules in that studies in Drosophila and C. elegans encoding homologs of mammalian NOTCH1 indicate that RBP-J acts downstream of NOTCHI. [16][17][18][19][20][21] RBP-J or suppressor of hairless (SuH), the Drosophila homolog of RBP-J , is a known transcriptional repressor capable of regulating transcription through numerous cellular and viral promoters by binding to its cognate sequence within promoter regions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, signaling by NOTCH1 can be mediated by its association with RBP-J and potential other factors acting at the promoters. [12][13][14][15] Genetic studies have also suggested a functional association with these two molecules in that studies in Drosophila and C. elegans encoding homologs of mammalian NOTCH1 indicate that RBP-J acts downstream of NOTCHI. [16][17][18][19][20][21] RBP-J or suppressor of hairless (SuH), the Drosophila homolog of RBP-J , is a known transcriptional repressor capable of regulating transcription through numerous cellular and viral promoters by binding to its cognate sequence within promoter regions.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Su(H) is thought to be dependent on a direct physical interaction with the Notch cytoplasmic domain. Homologs of these proteins have been described in Xenopus (Wettstein et al 1997), mouse (Matsunami et al 1989), and humans (Amakawa et al 1993) suggesting a high degree of evolutionary conservation. For example, the mammalian homolog of Su(H), CBF1/RBP-J , can bind and stimulate promoters of the mouse Hairy enhancer of split (HES-1) genes in the presence of vertebrate Notch (Jarriault et al 1995).…”
mentioning
confidence: 99%
“…The sequences of two peptides from each of the 56-and 61-kDa forms were obtained. All four sequences were identical to the previously cloned murine homolog of the Drosophila transcription factor Su(H) (39,40), also known as CBF1 (41). The positions of the peptide sequences relative to the sequence of Drosophila Su(H) and murine CBF1 are shown in Fig.…”
Section: Identity Of Hs2nf5 As the Mammalian Homolog Of Su(h) Cbf1-mentioning
confidence: 76%
“…A General Role for Notch Signaling in Hematopoietic Cells?-CBF1 was first purified from a pre-B-cell line, based on its binding to the J recombination signal (41). It was later revealed that a CBF1-binding site was created by the concatamerization of this sequence (42).…”
Section: ␤-Globin Lcr and Notch-regulated Factor Cbf1mentioning
confidence: 99%
See 1 more Smart Citation